Perancang Data Warehouse Dan Visualisasi Data Mutu Penerimaan Beras - Nita Chairunnisa; Dedy Sugiarto; Teddy Siswanto (Penerbitan Universitas Trisakti, 2022)
Rice is a staple food consumed by a large portion of the Indonesian population. Each region has its own rice production so that it has different qualities.. Indonesia itself has specific standards for good quality rice. In order for rice can be distributed evenly throughout the archipelago, Indonesia has a rice management organization, one of which is PT Food Station Tjipinang Jaya. Rice from various suppliers must be recorded and checked for quality. Making a Data Warehouse needs to be implemented so that it is easily collected and analyzes the data received and can be used as a reference for decision making. To build a data warehouse can use Extract, Transform and Load (ETL) available in Pentaho Data Integration. Data that has been entered into the data warehouse can be visualized using Python to make further decisions.